Effects of Zn Addition on Microstructural Evolution, Mechanical Properties, and Corrosion Resistance of Al‐6Mg Alloy Subjected to Equal Channel Angular Pressing Processing at 200 °C. Issue 2 (23rd November 2022) - Guo, Yanping; Gao, Chao; Yang, Xiaohui; Ku, Tingting; Wang, Linzeng; Yang, Wenlu; Hu, Rujie; Cui, Jianyu; Chen, Huiqin
Abstract : The evolution of microstructure, mechanical properties, and corrosion performance of Al‐6Mg and Al‐6Mg–1Zn alloys processed using equal channel angular pressing (ECAP) at 200 °C is systematically investigated. Microstructural analysis reveals that different T and β phases are generated in the two studied alloys, resulting in different grain refinement processes. The average size of T phase in Al‐6Mg–1Zn alloy increases first and then decreases, and the distribution of T phase inside grains becomes denser with increasing ECAP deformation. The continuity of T phase at the grain boundary increases from 0 to 2 passes and decreases from 2 to 4 passes. In contrast, the β phase in Al‐6Mg alloy mainly locates at grain boundaries and becomes coarser and more continuous from 0 to 4 passes. The fracture strength of Al‐6Mg–1Zn alloy after 4‐pass ECAP reaches 391 MPa with a fracture elongation of 28%, which is superior to that of 4‐pass ECAP Al‐6Mg alloy. The 4‐pass ECAP Al‐6Mg–1Zn alloy has a higher corrosion resistance compared to the Al‐6Mg alloy under the same deformation condition. The low corrosion susceptibility in 4‐pass ECAP Al‐6Mg–1Zn alloy is attributed to sparse distribution of the T phase along the grain boundary. Abstract : The 4‐pass equal channel angular pressed (ECAPed) Al‐6Mg–1Zn alloy achieves superior mechanical properties and corrosion resistance compared with the 4‐pass ECAPed Al‐6Mg alloy due to the massive nanoscale T phase inside grains and sparse distribution at grain boundaries.